(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
Conversational conventions vary among cultures and languages. One conversational convention may be acceptable in one culture but may be termed unacceptable in another culture. Among Nigerian users/speakers of English, interruption is one of the controversial conversational strategies in conversation which may or may not be acceptable to participants. Interruption can also trigger conflict in a situation that is not acceptable. In family discourse, it could serve as a yardstick to measure power relations among members. This study, therefore, investigates the use of interruption in family conversations. It also examines whether interruption stimulates family conflict. Sacks, Schegloff, and Jefferson’s conversational analysis (CA) serve as the theoretical framework. The data used for this research was collected from an edition of Wale Adenuga’s Super Story: Because You Loved Me. The data was obtained by reproducing and recording the audio aspect of the drama. This was then transcribed based on the transcript convention of conversational analysis. The data was analyzed using qualitative means. The patterns observable were then related to the context. The findings show that interruption, even though could be a strategy in conversation, brings about conflict among participants in family discourse.